Photographic silence: Remediating the graphic to visualize migrant experience in Shaun Tan's The Arrival. Issue 2 (1st November 2020) - Singh, Amrita
In the absence of a verbal language, The Arrival's mode of representation is derived from various visual storytelling practices in addition to the comic. This article proposes that Tan remediates the mode of comics storytelling by presenting the narrative as a photo album and drawing the panels as photographs, and in turn the photograph is also remediated in the text as a drawn object. Using transmedial techniques such as focalization, gaze, framing and page layout, in addition to deliberations on style and form, Tan constructs comics storytelling with a photographic vision. This photographic vision is used to represent the experience of migration in the narrative as well as connect past and contemporary histories of migration world over. The photograph emerged as an important medium through which memory came to be visualized in the twentieth century, and is an important historical artefact capable of telling the story of its times. Tan also expects the reader to employ an intermedial and intertextual critical literacy to engage with the narrative. The visual poetics of the text direct the reader's affective and empathetic engagement with the situation being presented and with the character whose experience they encode. The article focuses on three kinds of photographic representation in the narrative: the iterations of the protagonist's family photograph, the narrative itself shaped as a photo album and the immigrant's identification photograph.